Manhaj Taâlim al-Lughati al-Arabiyati li Ghairi al-Natiqina Biha Min al-Jaliyah al-Arabiyati (Dirosah Muqoronah) - Fauzun Jamal (Indonesian Journal of Arabic Studies, 2020)
The countries of Tunisia and Morocco have a diaspora community abroad and they are like those who speak non-Arabic from other peoples, because of the circumstances surrounding them that make the vocabulary and first terms in the linguistic and communication memory for them are the vocabulary and terminology of the country in which it resides. The Bourguiba era for living languages in Tunisia and the West Islamic Institute in Morocco are among the Arab foundations that enjoy the establishment of a special Arabic language education program for the Arabic diaspora. The two institutes have drawn curricula and teaching methods with goals and challenges. This research attempted to reveal the following problem: How is the educational experience of the Arab community in the two institutes carried out in front of educational teams? How did the two institutes develop their Arabic curricula towards the requirements of the times? By employing the comparative descriptive approach, starting from collecting data and reports that summarize points and ideas to build their curricula and clarifying similarities, differences and what are the prevailing conditions in them.